Validation to Spanish of nursing assessment scale for early diagnosis of delirium - Nu-DESC - Henao-Castaño, Ángela María; Lozano González, Linamaría; Gómez Tovar, Luz Omaira (Investigación y Educación en Enfermería, 2023)
Objective. This work aimed to determine the validity and reliability of the Colombian Spanish version of the Nursing Delirium Screening Scale (Nu-DESC). Methods. A psychometric study was conducted to achieve the goal of this study, which measured face validity, content validity, sensitivity, specificity and predictive values of the Nu-DESC. Results. Face validity obtained a total Aiken V of 0.89, and content validity showed a modified Lawshe index of 0.92. When Nu-DESC was applied to 210 adult patients hospitalized in the Intensive Care Unit, it was found that 14.2% had suspected delirium. The instrument showed a sensitivity of 91.6%, specificity of 95.6%, positive predictive value of 73.3%, negative predictive value of 98.8%, good internal consistency with Cronbach's α of 0.8 and good concordance according to Cohen's Kappa index of 0.788. Conclusion. The Spanish version of the Nu-DESC scale for Colombia has appropriate psychometric values for assessing delirium risk. In addition, this scale is easy to apply, so the adaptation of nursing personnel for its employability favors routine monitoring and timely detection of delirium.